IMPLEMENTASI METODE SILENT WAY DALAM PEMBELAJARAN BAHASA ARAB DENGAN MEDIA KARTU BERGAMBAR UNTUK MENINGKATKAN PENGUASAAN MUFRADAT SISWA KELAS VI - Zaky, Muhammad; Fauziah, Asti; Zulhannan; Nur, Robiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of the Silent Way method in Arabic language learning using picture card media to enhance vocabulary mastery among sixth-grade students at SD Islam Assalam Bandar Lampung. This study employs a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, conducted in two cycles. Data were collected through vocabulary mastery tests, observations, and interviews with teachers and students. The findings indicate that the Silent Way method combined with picture card media significantly improves students’ vocabulary acquisition. In the first cycle, the mastery level reached 60%, whereas in the second cycle, it increased to 88%, demonstrating substantial improvement. This method also enhances student engagement and motivation in Arabic language learning. In conclusion, the Silent Way method with picture card media can serve as an effective alternative strategy to improve vocabulary mastery among elementary school students. This study recommends the broader implementation of this method and further exploration of technology integration in its application.